Input Allocation, Workforce Management and Productivity Spillovers: Evidence from Personnel Data - Amodio, Francesco; Martinez-Carrasco, Miguel A (Review of Economic Studies, 2018)
This article shows how input heterogeneity triggers productivity spillovers at the workplace. In an egg production plant in rural Peru, workers produce output combining effort with inputs of heterogeneous quality. Exploiting variation in the productivity of inputs assigned to workers, we find evidence of a negative causal effect of an increase in coworkers¿ daily output on own output and its quality. We show theoretically and suggest empirically that the effect captures free riding among workers, which originates from the way the management informs its dismissal decisions. Our study and results show that input heterogeneity and information on input quality contribute to determine the shape of incentives and have implications for human resource management, production management, and the interaction between the two. Counterfactual analyses show that processing information on inputs or changing their allocation among workers can generate significant productivity gains.